Association of Adolescent Sport Participation With Cognition and Depressive Symptoms in Early Adulthood. Issue 9 (26th September 2019) - Bohr, Adam D.; Boardman, Jason D.; McQueen, Matthew B.
Background: Recent studies have associated sport-related concussion with depression and impaired cognitive ability later in life in former professional football players. However, population studies with two 1950s-era cohorts did not find an association between high school football participation and impaired cognition or depressive symptoms in late adulthood. Purpose/Hypothesis: This study assessed whether actual/intended participation in contact sports during adolescence had an adverse effect on participants' cognition or depressive symptoms in early adulthood. We hypothesized that there would not be an association. Study Design: Cohort study; Level of evidence, 2. Methods: This study used a subsample (n = 10, 951) from the National Longitudinal Study of Adolescent to Adult Health (Add Health), a nationally (United States) representative prospective cohort study following participants through 4 waves of data collection from 1994 through 2008. Participants were categorized as actual/intended participation in no sports, noncontact sports only, and contact sports. We constructed 6 multivariate and logistic regression models predicting word recall, number recall, modified Center for Epidemiologic Studies Depression Scale, depression diagnosis, suicide ideation, and suicide attempts at wave IV as a function of sport participation during wave I. Sport participation was treated as a factor with the referent category noncontact sports. This analysis was repeated on a males-only sample (n = 5008). In the males-only analysis, participants were classified as actual/intended participation in no sports, noncontact sports, contact sports other than American football, and American football. The referent category remained noncontact sports. Results: Intention to participate in contact sports was not significantly associated with any of the outcomes in the full-sample analysis. Intention to participate in football was significantly associated with a reduced odds of depression diagnosis in adulthood (odds ratio, 0.70; P = .02) when compared with noncontact sports participation in the males-only sample. Football was not significantly associated with impaired cognitive ability, increased depressive symptoms, or increased suicide ideation. Conclusion: Actual/intended participation in contact sports during adolescence did not adversely affect Add Health participants' cognition or depressive symptoms in young adulthood.